SDN NETWORK CONCEPTS USING FOR TRAFFIC DISTRIBUTION BETWEEN LTE AND Wi-Fi NETWORKS - Одарченко, Р. С.; Ткаліч, О. П. (Science-based technologies, 2014)
The paper proposed a method of structure LTE network improving by utilizing the concept of HotSpot 2.0, which allows you to provide support automatic mobile devices login in the network and secure access to partner Wi-Fi networks. SDN concept using is proposed for coordinated control of the entire network, which will significantly reduce the cost of the network operating, as well as the introduction of new services.